Life is for Living: Claiming Past, Present and Future (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
Existential therapy distinguishes itself by addressing the whole of human existence and by considering an individual’s experience from a philosophical perspective. It calls each of us to a more deliberate way of life and invites us to a considered reflection on our own existence. It is easy to get out of touch with these fundamental givens of the existential approach as we struggle to define our methods and techniques in a world that sets great store by qualifications, standards and evidence based practice. It is important to remember the most elemental aspects of what we do, so that we can build on them for the future. This paper takes stock of what really matters and what we often forget. It reengages with the radical project of making sense of our lives, asking how space and time figure in our lives and what values we want to live by. How shall we approach the pressures and strains of a demanding yet fragile world and how shall we respond to an ever growing sense that there must be more to life than this? What old or new philosophy can save us from the tedium or chaos of our lives? When you look back upon what you have accomplished in the days that are given you, what will remain as the guiding light?